Trypanosoma brucei Infection Stimulates Receptor-Mediated Phagocytosis by Murine Peritoneal Macrophages - Fierer, Joshua (1982)
Trypanosoma brucei infection results in hypertrophy of the reticuloendothelial system. Peritoneal macrophages from infected mice were larger, spread out more on glass, and had increased receptor-mediated phagocytic activity both for C3b-and immunoglobulin G-coated erythrocytes. These observations suggest that macrophages were activated as a result of this infection.